Digital boundaries: A study on WeChat parent-child relationships among Chinese college students and their association with family factors. - Zhao Feng; Chun-Mei Hu; Ling-Ling He (PLoS ONE)
Objective This study aims to investigate the current state of WeChat parent-child relationships among college students and their association with family factors. Methods Using convenient sampling, 6159 students,age from 18 to 25,the participants were selected from colleges of Chengdu to complete a questionnaire survey on response and attitudes towards parents' WeChat friend requests, Family APGAR Index,Parental Management Scale,Family Conflict Scale,were used as measurement tools. Results Responses to parental WeChat friend requests showed significant positive correlations with higher levels of family function satisfaction (r = 0.10, P<0.01) and parental management (r = 0.11, P<0.01), and a significant negative correlation with family conflict (r = -0.03, P<0.05). Conclusion This study reveals that Chinese college students generally accept their parents' WeChat friend requests, influenced by family dynamics and traditional values. Positive parental management, family harmony, and good marital relationships enhance students' willingness to connect with their parents on WeChat, indicating the complex interplay between digital interactions and traditional family concepts.This underscores the importance for parents to adopt modern and scientific parenting approaches, fostering a harmonious and nurturing family atmosphere rooted in trust and mutual respect for their children.